No-clear-cause intra-cerebral hemorrhage: subtypes, causes and mechanisms - Schreiber, Stefanie (Henry Stewart Talks, 2024)
Lobar, deep, cerebellar and intraventricular hemorrhages, Locations of spontaneous hemorrhages, Main causes, Edinburgh criteria, Cerebellar amyloid angiopathy (CAA), Hypertensive arteriopathy (HA), Finger-like projections (FLP), Subarachnoid hemorrhage (SAH)